Valenţa juridică a clasificării contractelor civile [Articol] - Cimil, Dorin (Institutul Naţional al Justiţiei, 2017)
În acest studiu am încercat să abordăm aspectul practic al teoriei de clasificare a contractelor. Am reuşit să analizăm efectele juridice specifice unui anumit tip de contracte în funcţie de clauzele specifice stipulate de părţi sau chiar de legiuitor. Astfel, abordarea noastră ştiinţifică a fost orientată spre înţelegerea unor construcţii contractuale complexe care unifică într-o singură formă elemente considerate a fi antagonice.

In this study we tried do render a practical content for the theoretical subject of contract classification. We managed to analyze the particular juridical effects of a certain type of contracts, depending on the specific clauses that they have embraced by the will of the parties or even the legislator. Thus, our scientific approach was ori ented to the understating of complex contractual constructions that unify under unique form elements considered to be antagonistic.
The legal value of the civil contracts’ classification
Keywords: contracte civile; Codul Civil; contracte negociate; civil contracts; the Civil Code; negotiated contracts